Scented facemask / Nurul Nabilah Rosli … [et al.] - Rosli, Nurul Nabilah; Baharom, Siti Nurhafizah; Mohd Zulkepli, Nur Hazwani; Arsat, Nur Arifah Amirah; Abas, Norlela (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Global pandemic COVID-19 circumstances emerged in an epidemic of dangerous disease in all over the world. Wearing a face mask will help prevent the spread of infection and prevent the individual from contracting any airborne infectious germs. Since there is no specific treatment, wearing masks has become an effective method to prevent the transmission of COVID-19 and is required in most public areas, which has also led to a steadily growing customer demand for face mask .Using Scented Face Mask , we can guarantee if the people are wearing our masks in a comfortable condition since it provide a smell that suitable for all .